2003
DOI: 10.1038/sj.gt.3302122
|View full text |Cite
|
Sign up to set email alerts
|

In vivo adenovirus-mediated delivery of a uPA/uPAR antagonist reduces retinal neovascularization in a mouse model of retinopathy

Abstract: Diabetic retinopathy and retinopathy of prematurity are among the leading causes of vision impairment throughout the world. Both diseases are characterized by pathological angiogenesis, which severely impairs vision. Extracellular proteinases play important roles in endothelial cell migration during angiogenesis. Amino-terminal fragment (ATF) is an angiostatic molecule that targets the uPA/uPAR system and inhibits endothelial cell migration. The angiostatic effect of ATF has been demonstrated in models of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…It has been shown that constitutive activation of p38alpha is required for uPA/uPAR expression and matrix invasion by breast cancer cells (Huang et al, 2000). Inhibition of the uPA/uPAR system by uPAR gene deletion, pharmacological inhibitors or adenoviral delivery of the noncatalytic amino-terminal fragment of uPA reduces neovacularization in a mouse model of retinopathy of prematurity (Le Gat et al, 2003; McGuire et al, 2003). A recent study also demonstrated the critical role of p38 in regulating chronic inflammation-mediated angiogenesis through MMPs, the downstream target of uPA/uPAR system (Rajashekhar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that constitutive activation of p38alpha is required for uPA/uPAR expression and matrix invasion by breast cancer cells (Huang et al, 2000). Inhibition of the uPA/uPAR system by uPAR gene deletion, pharmacological inhibitors or adenoviral delivery of the noncatalytic amino-terminal fragment of uPA reduces neovacularization in a mouse model of retinopathy of prematurity (Le Gat et al, 2003; McGuire et al, 2003). A recent study also demonstrated the critical role of p38 in regulating chronic inflammation-mediated angiogenesis through MMPs, the downstream target of uPA/uPAR system (Rajashekhar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier results about the possibility to reduce neovessel formation in the retina by pharmacological interaction with the uPA/uPAR system can be traced back to 2003 when Le Gat et al have demonstrated anti-angiogenic efficacy of intravitreal delivery of ATF in a mouse model of OIR. As ATF binds to uPAR on the cell surface, it blocks the interaction between uPA and uPAR thus inhibiting uPA/uPAR-dependent neovascular tuft formation [53]. This study was the proof of concept that molecules disrupting the interaction between uPA and uPAR might be effective in counteracting retinal neovascular pathologies.…”
Section: Inhibition Of the Upar Systemmentioning
confidence: 93%
“…After the two-chain uPA is cleaved by a second round of proteolysis, a single chain form of uPA, which is about 250 times more active than the two-chain form, is generated together with an inhibitory amino-terminal fragment (ATF) (for Ref., see [52]). ATF binding to uPAR affects the interaction between uPA and uPAR with a consequent inhibition of the functional effects of uPAR activation (for Ref., see [53]). uPA binding to uPAR increases the activation of plasminogen into plasmin that is involved in the dissolution of ECM and basement membrane during tissue degradation (for Ref., see [52]).…”
Section: The Upar Systemmentioning
confidence: 99%
“…This may explain why proliferative retinopathies are associated to overexpression of uPA/uPAR, which appears to be essential for the development of new vessels in the retinas of diabetic mice and rats [10,15]. This role has been confirmed by findings indicating that uPA/uPAR system inhibition or uPAR gene deletion prevent the increase in retinal vessel permeability in rodent models of ROP, DR and AMD, and reduce pathologic angiogenesis in mouse models of ROP and AMD [11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 84%